Governing indigenous territories: enacting sovereignty in the Ecuadorian Amazon - Erazo, Juliet S. (Duke Univ. Press, 2013)
Contents; List of Maps; Selected Acronyms; Acknowledgments; Preface; Introduction; One: History, Empowerment, and Rule; Two: Collectivist Utopias and "The Graveyard of Development Projects"; Three: The Property Debate; Four: Conservation and Environmental Subjects; Five: Everyday Forms of Territory Formation; Conclusion: Making Citizens, Making Leaders, Making Territories; Appendixes; Notes; References; Index